Relationship between Knowledge Level and Attitude with Ovarian Cancer Early Detection Behavior at Ibnu Sina Hospital Makassar - Raihan Aulia Arbani; Shofiyah Latief; Febie Irsandi Syahruddin; Hamsah Hamsah; Berry Erida Hasbi (Universitas Muslim Indonesia, 2023)
Ovarian cancer is a malignant tumor originating from the ovary with various histological types that can affect all ages, in the early stages of the disease does not show specific clinical symptoms. The Indonesian Society of Gynecologic Oncology recorded 354 cases of ovarian cancer and is the second most common gynecologic cancer. The high mortality rate is due to asymptomatic tumor growth, delayed onset of symptoms, and lack of proper screening so that ovarian cancer is only diagnosed at an advanced stage. Ovarian cancer cases that are recognized and found at an early stage and receive rapid and appropriate treatment and treatment will provide a better life expectancy. Currently, radiologic examinations for ovarian cancer detection include: Ultrasound, CT scan, PET scan, and MRI. This study aims to determine the relationship between the level of knowledge and attitudes with the behavior of early detection of ovarian cancer at Ibnu Sina Hospital Makassar. Research using quantitative descriptive design with cross-sectional design. Of the 60 respondents obtained results based on the category of knowledge level in patients diagnosed with ovarian cancer who have good knowledge as many as 19 respondents (100%), enough as many as 10 (41.7%), less (5.9%) good category attitudes as many as 18 (40.9%), enough 12 (80.0%), less 0 respondents (0.0%). And for the level of knowledge in patients who are not diagnosed with ovarian cancer who have good knowledge 0 respondents (0.0%), enough 14 (58.3%), less knowledge as many as 16 (94.1%), good category attitudes 26 (59.1%), sufficient category attitudes 3 (20.0%), less category attitudes 1 (100.0%). There is a relationship between the level of knowledge and attitude towards ovarian cancer early detection behavior.